Morphological substantiation of application of a method laser thermodestruction in neurooncology - Rozumenko, V.; Semenova, V.; Nosov, A.; Khomenko, O.; Vaslovich, V.; Tyagliy, S.; Othman, O. (Ukrainian Neurosurgical Journal)
On the basis of the analysis of experimental researches optimum parameters of continuous and pulse modes of a laser irradiation concerning maintenance of effect laser thermodestruction in a tumoral tissue are established. Determined destructive changes have characteristic ash value of damages with formation of coagulated tissue zones, necrobiosis and pericellular edema. Amplification of irreversible destruction changes in the remote period of LTD reflects the deferred effect laser thermodestruction.